ITEM ANALYSIS OF ENGLISH SUMMATIVE TEST BASED ON ITEM RESPONSE THEORY (IRT) - Maria Lumbantoruan; Indra Hartoyo (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This study aims at finding out the indices of English summative test as well as describing the test quality based on the 3-PLM of IRT (Item Response Theory). A descriptive-quantitative design is applied by using Rstudio program to analyze the data. The findings show that there are three indices in evaluating English test based on the 3-PLM of IRT, they were item difficulty (b -parameter), item discrimination (a -parameter) and pseudo guessing (c -parameter). As much as 95 % (38 items) are in the good category of difficulty index and 5% (2 items) are in the poor category/very easy items. Then, as much as 30 % (12 items are in the good category and 70 % (28 items) in the poor category of the discrimination power. While referring to the guessing parameter, as much as 90 % (36 items) are in the good category and 10 % (4 items) are in the poor categoryKeywords: Item Analysis, Summative Test, IRT